ΟΙ ΠΕΛΟΠΟΝΝΗΣΙΑΚΕΣ ΠΟΛΕΙΣ ΚΑΙ Η ΜΕΤΑΣΤΟΙΧΕΙΩΣΗ ΤΟΥ ΠΛΗΘΥΣΜΟΥ ΤΟΥΣ ΚΑΤΑ ΤΗ Β' ΒΕΝΕΤΟΚΡΑΤΙΑ. ΤΟ ΠΑΡΑΔΕΙΓΜΑ ΤΗΣ ΤΡΙΠΟΛΙΤΣΑΣ - ΝΤΟΚΟΣ, ΚΩΝΣΤΑΝΤΙΝΟΣ; ΒΑΣΙΛΑΚΗ, ΚΑΤΕΡΙΝΑ; ΒΙΟΛΙΔΑΚΗΣ, ΓΕΩΡΓΙΟΣ; ΛΕΜΠΕΣΗ, ΣΤΕΛΛΑ; ΜΑΝΔΗΛΑ, ΜΑΡΙΑ; ΜΗΤΟΥΛΑΚΗΣ, ΔΗΜΗΤΡΙΟΣ; ΠΕΡΡΑ, ΦΩΤΕΙΝΗ; ΠΕΣΛΗΣ, ΚΩΝΣΤΑΝΤΙΝΟΣ (Eoa kai Esperia, 2003)
When the Venetians dominated the Péloponnèse and the so called SecondVenetian dominion began, all the Turks withdrew from the region. On the contrary,many colonists from the surrounding areas of the Turkish-occupied Greece came tosettle in that area.Therefore, a true change was observed in the configuration of the wholePeloponnesian population. Based on an unpublished, till now, Italian document ofthe Venetian archives dated back to 1698, this historic phenomenon is investigatedin particular in Tripolizza, a provincial town of the Venetian Péloponnèse.